1993
DOI: 10.1097/00006842-199301000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Hostility and myocardial ischemia in coronary artery disease patients: evaluation by gender and ischemic index.

Abstract: Two studies assess relationships of hostility to extent and severity of exercise-induced cardiac ischemia and daily life ischemia in patients with coronary artery disease (CAD). CAD patients (N = 80) who underwent exercise tomographic thallium testing to assess myocardial perfusion completed the Cook-Medley Hostility Inventory (Ho). A Composite Hostility (Chost) score obtained from the Ho scale was also used. Statistically controlling for the effects of gender in the full sample (N = 80), Chost was positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…76,80 -82 In addition, studies have reported that CAD patients with high levels of hostility have a greater rate of restenosis after angioplasty, 83 experience more rapid atherosclerosis progression during serial carotid ultrasonography, 84,85 and manifest more ischemia during stress testing than other CAD patients. 86 …”
Section: Personality and Character Traitsmentioning
confidence: 99%
“…76,80 -82 In addition, studies have reported that CAD patients with high levels of hostility have a greater rate of restenosis after angioplasty, 83 experience more rapid atherosclerosis progression during serial carotid ultrasonography, 84,85 and manifest more ischemia during stress testing than other CAD patients. 86 …”
Section: Personality and Character Traitsmentioning
confidence: 99%
“…35 Parallel ambulatory studies in coronary artery disease patients in daily life show similar results 38 and have been extended to demonstrate that both the intensity of mental effort and the presence of negative mood correlate with myocardial ischemia. In addition, both ambulatory 38 and laboratory studies 39 have demonstrated correlations between hostility and ischemia in humans.…”
Section: Psychosocial Variables and Myocardial Ischemiamentioning
confidence: 99%
“…This hostility scale was initially developed to differentiate between teachers having good versus bad rapport in their relationships with students, but has become popular among health outcomes researchers as the evidence accumulates suggesting it is an important predictor of future cardiovascular health status (see Smith, 1992 Helmers and Krantz (1996) reported a mean of 21.03 (± 6.9) in their study of 68 healthy men and women. Helmers et al, (1993) reported a mean of 16.9 (± 5.9) in a sample of 63 men with CAD and a mean of 14.6 (± 8.6) in a sample of 17 women with CAD. The questionnaire as provided to the participants is included in the appendix.…”
Section: Hostilitymentioning
confidence: 97%
“…In general, researchers suggest the Ho scale reflects cynical beliefs and mistrust (Barefoot & Lipkus, 1994). Other studies have continued to implement the Composite Hostility score in assessing hostility-health relationships (Suarez & Williams, 1989;Helmers et al, 1993;Helmers et al, 1995).…”
Section: Hostility Assessmentmentioning
confidence: 99%
See 1 more Smart Citation